Frequency of the rs 14035 polymorphism of RAN gen in recurrent pregnancy loss: A case-control study - Zahrasadat Mortazavifar; Hamidreza Ashrafzadeh; Seyed Morteza Seifati; Nasrin Ghasemi (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Genetic factors could account for recurrent pregnancy loss (RPL). The RAN gene is a member of the "large RAS family" and a small GTPase that is essential for the translocation of Ribonucleic acid (RNA) and proteins through the nuclear pore. Mutation in the RAN constitutive gene could stop DNA synthesis and alter the expression of genes in the uterus, likely playing a role in recurrent miscarriage. Objective: The aim was to investigate the frequency of RAN (rs 14035) polymorphism in women with RPL compared with women without abortion history. Materials and Methods: In this case-control study, 100 women with at least two consecutive miscarriages before the 20th wk of gestation and having spouses with karyotype and normal sperm parameters as the case group and 100 women with no history of abortion and having at least one successful pregnancy and normal delivery as the control group. The groups were age matched (20-40 yr). The rs 14035 polymorphism of RAN gene was investigated by Polymerase Chain Reaction-Restriction Fragment Length poly morphism technique and the frequency of which was compared between the two groups. Results: The frequency of TT, TC, and CC genotypes of RAN gene polymorphism in the case group were 9%, 40%, and 51%, respectively, and in the control group were 11%, 38%, and 51%, respectively. There was no significant difference in the genotypes between two groups (p = 0.882). Conclusion: According to our results, it seems that RAN polymorphism (rs 14035) is not associated with the risk of RPL in this study population.